ENDANGERED MEDIA BERBASIS MULTIMEDIA UNTUK PEMBERDAYAAN GURU-GURU SEKOLAH MINGGU (SUNDAY SCHOOL) - Titi Nur Vidyarini; Gatut Priyowidodo (Institute of Research and Community Outreach - Petra Christian University, 2014)
The community service was conducted to introduce multimedia-based teaching or in class communication method. The program is targeting Sunday school teachers or known as Pamong Kebaktian Anak (Kid’s church) at GKJW Madiun Lor in Madiun and GKJW Rungkut in Surabaya. The class emphasised on the use of verbal and nonverbal communication method, or traditional media. Nowadays the development of multimedia has touched the children and teenagers who learn informal religion education of Sunday School. Through this activity, we tried to introduce the use of multimedia, such as laptop, tablet and video clip application in the teaching process. The first stage is to know the characteristic of the children or target audience. The next stage is to introduce the multimedia application.